Magnetic clouds and origins in STEREO era. Issue 5 (14th May 2014) - Yan, Li; Luhmann, J. G.; Lynch, B. J.; Kilpua, E. K. J.
Abstract When a coronal mass ejection (CME) encounters the Earth, the Earth's electromagnetic environment is disturbed, especially when it is a magnetic cloud (MC) with enhanced, steady, and long‐lasting southward field. The speed and the magnetic field of an MC are the two important properties for its geoeffectiveness. The correspondence between a CME and its resulting MC is not straightforward, partly due to the CME velocity and the complications during propagation through corona and the solar wind. From 2007 to 2012, we have three observing points at 1 AU near the ecliptic plane (ACE and STEREO A and B). We search for MC events encountered at one of the three observers and study the statistics independently and in comparison. We found that the annual number of MCs at each receiver varies significantly and the temporal variation at each receiver does not always follow the solar activity level. The speed and the magnetic field strength of the MCs do vary with the solar activity level. The polarity of MC magnetic field at ACE and STEREO also shows large fluctuations. We have also identified the CME and solar activity sources for the L1 MC events. STEREO SECCHI images served critical roles in the determination of the CMEs both in solar quiet times and active times. We found that halo CMEs are not necessarily good indicators for receiving MCs. Further studies of CME initial velocity and the propagation through the heliosphere are needed in order to improve our space weather forecasting capability.